STUDI LITERATUR: EFEKTIVITAS PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PBL (PROBLEM BASED LEARNING) - Sukmawati Dwi Setiyaningsih; Lulu Dwi Lestari; Lutfi Nur Kharisma; Elza Rachmawati Zahra; Kafita Risma Kamelia; Mia Serawati Gangsarulloh; Niken Larasati; Lismawati; Gigih Winandika (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The purpose of this article is to determine the effectiveness of social studies learning using the PBL (problem based learning) learning model in elementary schools. Social Sciences (IPS) is a learning program that studies social life in the form of history, geography, economics and sociology. In the world of education, there are several methods that can be applied in social studies learning in elementary schools, one of which is PBL (Problem Based Learning) which can train students to learn knowledge content and solve problems in real life. This discussion needs to be done because humans need it in real life and make it easier for teachers to carry out the teaching and learning process in schools so that learning objectives are achieved. So the author chose the title of the effectiveness of social studies learning using the PBL (problem based learning) learning model in elementary schools. This study uses a literature review research design. The data collection technique uses a national article literature study in 2020-2025. The results of this study obtained 10 articles according to the focus of the study. The results of the research analysis have the same statement, namely that the PBL (Problem Based Learning) learning model has effectiveness and can help in the learning process.